Morphology and charge recombination effects on the performance of near-infrared photodetectors based on conjugated polymers - Lee, Dae Woon; Kang, Yeongkwon; Jo, Bong Hyun; Jeon, Gyeong G.; Park, Jaehong; Yoon, Sang Eun; Zheng, Jian; Ahn, Tae Kyu; Park, Hui Joon; Kim, Bong Gi; Kim, Jong H. (Organic Electronics, 2019)
Near-infrared (NIR) photodetectors sensitive to 860 nm light were fabricated through a solution process using two different conjugated polymers (CPs) that share a similar conjugated backbone consisting of a diketopyrrolopyrrole (DPP) moiety. The two CPs had a comparable conjugated nature, but their detection capabilities were significantly different depending on the applied linker units, namely thiophene for PDPP-T and fluorinated thiophene for PDPP-FBT. First, we revealed that employing an additive during active film preparation was beneficial for achieving an optimum film morphology for both CPs, which could suppress dark current and provide enhanced detectivity. In addition, when a highly electronegative fluorine atom, which induces a surface dipole, was introduced into the conjugated skeleton, it was clearly demonstrated via transient photovoltage measurements that the charge recombination time was lengthened, which implies an increase in the probability of charge extraction in actual devices by suppressing charge recombination. Thus, PDPP-FBT exhibited higher external quantum efficiency and responsivity across all wavelengths. Our results indicated that the management of both film morphology and surface dipoles of CPs are equally important for achieving high detectivity and responsivity in organic NIR photodetectors.
Keywords: Bulk heterojunction; Charge recombinations; Conjugated backbones; Detection capability; Diketopyrrolopyrroles; External quantum efficiency; Near infrared photodetectors; Transient photovoltage measurements; Bulk heterojunction; Charge recombination; Conjugated polymers; Dark current; Morphology; Near-infrared photodetector